Efecto de la fuente de carbohidratos sobre el balance energético-nitrogenado y las emisiones de metano de vacas lecheras lactantes - Posada-Ochoa, Sandra L. (2024)
The chemical characteristics of Cenchrus clandestinus grass, nutritional base in dairy production systems, demand the energy supplementation. Corn grain is the most used food for this purpose, but considering its demand and prices, the objective of this work was to evaluate its partial replacement by alternative non-fibrous carbohydrates sources on methane emissions, energy and nitrogen balance and productive performance of dairy cows. Sixteen multiparous Holstein cows were fed Cenchrus clandestinus plus one of four concentrate supplements formulated with corn (Zea mays) or a partial replacement of corn with sorghum (Sorghum vulgare), cassava (Manihot esculenta) or citrus pulp (Citrus sp.). Inclusion of sorghum, cassava or citrus pulp did not affect dry matter intake, dry matter digestibility, enteric methane emissions, energy and nitrogen balance, milk yield or composition. The results allow to conclude that these ingredients can partially replace corn in the diet of lactating dairy cows.